1992
DOI: 10.1177/001872089203400302
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Audible Movement Angle as a Function of the Azimuth and Elevation of the Source

Abstract: In the future auditory directional cues may enhance situational awareness in cockpits with head-coupled displays. This benefit would depend, however, on the pilot's ability to detect the direction of moving sounds at different locations in space. The present investigation examined this ability. Auditory motion acuity was measured by the minimum audible movement angle (MAMA): the minimum angle of travel required for detection of the direction of sound movement. Five experienced listeners were instructed to indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 14 publications
4
23
0
Order By: Relevance
“…The size of the error increases with greater vertical deviations from the horizontal plane as well as for locations behind the listener. Strybel et al (1992a) found LE in the vertical plane to be largest at 80° of elevation. In addition, Davis and Stephens (1974) observed that the vertical mean absolute error (MUE) decreased monotonically as sound intensity increased from a 10-dB sensation level (SL) to a 70-dB SL reaching a plateau at about 3.5° at a ~50-60 dB SL.…”
Section: Absolute Localizationmentioning
confidence: 93%
“…The size of the error increases with greater vertical deviations from the horizontal plane as well as for locations behind the listener. Strybel et al (1992a) found LE in the vertical plane to be largest at 80° of elevation. In addition, Davis and Stephens (1974) observed that the vertical mean absolute error (MUE) decreased monotonically as sound intensity increased from a 10-dB sensation level (SL) to a 70-dB SL reaching a plateau at about 3.5° at a ~50-60 dB SL.…”
Section: Absolute Localizationmentioning
confidence: 93%
“…Also of interest is the effect of dynamic change in facing angle. In the localization literature, differences have been found between the minimum audible angle (MAA) and the minimum audible movement angle (MAMA) (Chandler and Grantham, 1992;Harris and Sergeant, 1970;Mills, 1958;Perrott and Musicant, 1981;Perrott and Saberi, 1990;Strybel et al, 1992). It may be that differences between static and dynamic audible facing angles also exist.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum auditory angle (MAA) is the smallest separation between two sources that can be reliably detected. Strybel, Manligas and Perrott (1992) report that in the median plane sound sources only 1° apart can be detected. At 90° azimuth (directly opposite one ear) sources must be around 40° apart.…”
Section: Perception Of Soundmentioning
confidence: 94%